Conceptual design of outer tube inspection robot - Aziz M.A.; Jalal M.F.A.; Sahari K.S.M.; Leong Y.W.; Sekari S.A. (American Institute of Physics Inc., 2023)
Periodical maintenance and inspection of the power plant system and its subsystem are deemed necessary to avoid shortage and unplanned shutdown. Boiler is one of the main modules in thermal power plant. The boiler operates under high thermo and mechanical loading that leads to failures caused by degradation, creep, corrosion, and others. One of the critical area for inspection is the welding joint between the boiler header and tubes. In this paper, the conceptual design of the robotic system for inspecting the outer boiler tube condition specifically at the welding joint between the boiler header and tubes is presented. The main standard mechanical components namely passive actuator and motor are determine based on the detailed calculation. 2019 Author(s).